The Media Thematic Dictionary and Its Application in Improving Speaking Skills l Wasa’il al-Qamus al-Maudhu‘i wa Tathbiqu fi Tarqiyati Maharah al-Kalam - Syaifullah, Muhammad; Mubarokah, Siti; Izzah, Nailul; Putri, Wakhidati Nurrohmah; Nur, Kholida; Syuhadak, Syuhadak (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2023)
The Islamic Boarding School of Nahdlotul Ulum Metro faces challenges in teaching Arabic to elementary school students, resulting in limited vocabulary and boredom. This research aims to enhance students' speaking skills and vocabulary by employing thematic dictionaries. Conducted through qualitative field research, data was collected via observation, interviews with the head of the Islamic Boarding School, an Arabic teacher, and eight students, along with documentation. Employing technical and temporal triangulation, the researcher cross-verified information. After applying thematic dictionaries to improve speaking skills, students exhibited significant progress. They mastered Arabic letter writing, including recognizing letters at the beginning, middle, or end of words. The school's method of teaching alphabet basics and gradually introducing word formation contributed to this success. Students progressed from letter recognition to practical application in constructing words and speaking in Arabic. The positive outcomes underscore the effectiveness of thematic dictionaries in enhancing beginners' vocabulary and speaking skills. The research also presents a storyboard detailing the successful application of thematic dictionaries, offering a valuable resource for educators. This study contributes to addressing the initial challenges faced by the Islamic Boarding School, providing insights into practical methods for improving Arabic language instruction for elementary school students.